Encephalic Meningioma in Dogs - Chaves, Rafael Oliveira; beckmann, Diego Vilibaldo; Copat, Bruna; Feranti, João Pedro Scussel; de Oliveira, Marília Teresa; de Souza, Fernando Wiecheteck; Schwab, Marcelo Luís; Mazzanti, Alexandre (Acta Scientiae Veterinariae, 2016)
Background: Meningioma is the most common brain tumor in dogs. These extra-axial tumors originate in one of the meninges, and arachnoid is the most common. Several retrospective studies of brain tumors are found in the international literature. However there are few researches in the national literature. The purpose of this study is to report twelve dogs with brain meningioma. The breed, gender, age, neurological signs, the brain location, the clinical evolution, the tumor classifcation and diagnostics tests were investigated. Cases: Twelve dogs were attended at Veterinary Hospital of Santa Maria University: six mixed-breeds; four Boxer; a Dachs hund; and a Poodle. The age ranged from eight to 14 years, with average of ten years and nine months old. The clinical signs observed were generalized seizures (9/12); behavioral changes (6/12); walk in circle (5/12); swallowing diffculty (2/12 [16%]); hypermetria (2/12); central vestibular syndrome (1/12); and amaurosis (1/12). The presumptive diagnosis was brain neoplasm in all dogs. Six dogs were underwent symptomatic treatment with corticosteroids and anticonvulsants; two dogs were underwent corticosteroids; and four were euthanized without performing treatment. After starting treatment, four dogs (50%) showed clinical improvement in the frst week, however, the clinical signs worsened after two weeks. The thalamus-cortex region was affected in seven cases (59%), followed by cerebellar-pontine region (25%), brainstem (8%) and cerebellum (8%). In the histological classifcation of meningiomas, the meningothelial variant was observed in six dogs, three psammomatous, two transitional and a fbroblast. Discussion: The average age of initiation of clinical signs was ten years and nine months, similar result found in a large study about brain tumor. Female dogs were most affected (n = 8), although some authors did not report sexual predis position. The neurological signs of dogs with brain meningiomas occur through adjacent structures compression, direct invasion of tissues, interruption of circulation, edema, inﬂammation and necrosis. The thalamus-cortex region was the most affected and the seizures were the most common clinical signs observed in dogs, according to the international literature. The meningiomas canine are histologically classifed into two groups: benign tumors (meningothelial, fbroblast, transitional, psammomatous, angiomatous, papillary, myxoid and granular cells); and malignant tumors (anaplastic). The meningothelial variant was found most frequently in this stud (50%), according to the others authors. The clinical course of time was determined from the onset of signs found in neurological examination until the time of death or euthanasia of dogs, being progressive in all patients. In this study, encephalic neoplasms showed slow evolution of signals between fve to 180 days (mean 58 days). This time is longer compared to other study in which the mean survival of 86 dogs was 30 days. In the present study, there was only symptomatic treatment with corticosteroids and/or anticonvulsant. The conclusion of this study is that brain meningioma is a common tumor; occur in adult and older dogs of different breeds; the clinical signs more frequent were seizures, behavioral changes and walk in circle to the side of the lesion. The palliative treatment with corticosteroids and anticonvulsants may be effcient in controlling the clinical signs, however the long-term prognosis is adverse. Keywords: neoplasm, brain, neurology, dog.